2021
DOI: 10.1002/er.7240
|View full text |Cite
|
Sign up to set email alerts
|

Light‐trapping and spectral modulation to increase the conversion efficiency of triple‐junction GaAs solar cells using antireflective coating comprising a periodic array of cone‐shaped TiO 2 structures

Abstract: Summary This study sought to increase the conversion efficiency of triple‐junction GaAs solar cells via spectral light trapping through the application of a uniform TiO2 layer with an antireflective coating (ARC) comprising a periodic array of cone‐shaped TiO2 structures. The cone‐shaped TiO2 ARC structures were fabricated using a mask of polystyrene spheres (PS) of various diameters (600, 700, and 800 nm). This surface modification was meant to match external quantum efficiency (EQE) response and reflectance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The III-V compound solar cells represented by GaAs solar cells have attracted great attention in research community because of their high-efficiency potential, possibility of thinfilms, good temperature coefficient, radiation-resistance, and potential of multi-junction application [1][2][3][4][5]. The development of multi-junction solar cells has broken the limiting efficiency of single-junction solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The III-V compound solar cells represented by GaAs solar cells have attracted great attention in research community because of their high-efficiency potential, possibility of thinfilms, good temperature coefficient, radiation-resistance, and potential of multi-junction application [1][2][3][4][5]. The development of multi-junction solar cells has broken the limiting efficiency of single-junction solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tandem solar cells of III-V semiconductors can achieve the maximum efficiency, which benefits by an efficient utilization of the solar spectrum and lattice match. Especially, the case of Ge-based III-V triple-junction (TJ) solar cells [1][2][3][4][5] have attracted much attention, which has been widely applied in space for energy supply. To confine the misfit dislocation and minimize the strain, the previous study reported 6 that multijunction (MJ) III-V devices use compositionally graded buffers, which have demonstrated solar-to-electrical conversion efficiency of 39.2% (1 sun AM1.5G).…”
Section: │ Introductionmentioning
confidence: 99%